Strategi Komunikasi Pemasaran UMKM Rempeyek melalui Media Sosial TikTok untuk Meningkatkan Brand Awareness - Rohalia, Zakia; Sa'adah, Wardhatus; Ardiansyah, Muhammad Rafli; Nurjanah, Vike; Luayyin, Reza Hilmy (Universitas Pendidikan Nasional, 2025)
Social media has become an important tool in marketing communication for SMEs. TikTok, with its short video format, offers great potential to increase product brand awareness. This activity aims to optimize the marketing communication strategy of rempeyek SMEs through TikTok to expand their market reach. This public service used a Participatory Action Research (PAR) approach involving SMEs in training, mentoring, and evaluation. Data were collected through observation, interviews, and documentation, and analyzed descriptively. The results show improved digital skills, better use of TikTok features, and stronger consumer interaction. The strategy effectively enhances brand awareness while promoting rempeyek’s cultural value as a traditional Indonesian snack. Continuous digital training and cross-sector collaboration are recommended to sustain innovation and marketing competitiveness in the digital era.